2017
DOI: 10.1371/journal.pone.0171216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ESBL-Producing Enterobacteriaceae in Pediatric Bloodstream Infections: A Systematic Review and Meta-Analysis

Abstract: BackgroundPediatric bloodstream infections (BSIs) with Extended-Spectrum Beta-Lactamase- producing Enterobacteriaceae (ESBL-PE) are associated with worse clinical outcomes. We aimed to estimate the prevalence of and the mortality associated with ESBL-PE in this patient population.MethodsA systematic review and meta-analysis using PubMed and EMBASE and included studies reporting the prevalence of ESBL-PE among confirmed BSIs in patients <19 years old.ResultsTwenty three (out of 1,718 non-duplicate reports) stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 47 publications
2
52
0
3
Order By: Relevance
“…ESBL-E occur worldwide in both community and hospital settings (Paterson and Bonomo, 2005;Pitout et al, 2005;Sonda et al, 2016;Storberg, 2014;Luvsansharav et al, 2011), and the reported incidence of infections in paediatric and neonatal populations is increasing (Paterson and Bonomo, 2005;Sonda et al, 2016;Storberg, 2014;Flokas et al, 2017;Peirano and Pitout, 2010;Tansarli et al, 2014;Dramowski et al, 2015;Logan et al, 2014). Clinical infections with ESBL-E are associated with increased morbidity (including prolonged hospital stay), increased healthcare costs, and higher mortality rates compared to infections with non- ESBL-E (Blomberg et al, 2005;Zaoutis et al, 2005;Kim et al, 2002;Ndir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ESBL-E occur worldwide in both community and hospital settings (Paterson and Bonomo, 2005;Pitout et al, 2005;Sonda et al, 2016;Storberg, 2014;Luvsansharav et al, 2011), and the reported incidence of infections in paediatric and neonatal populations is increasing (Paterson and Bonomo, 2005;Sonda et al, 2016;Storberg, 2014;Flokas et al, 2017;Peirano and Pitout, 2010;Tansarli et al, 2014;Dramowski et al, 2015;Logan et al, 2014). Clinical infections with ESBL-E are associated with increased morbidity (including prolonged hospital stay), increased healthcare costs, and higher mortality rates compared to infections with non- ESBL-E (Blomberg et al, 2005;Zaoutis et al, 2005;Kim et al, 2002;Ndir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical infections with ESBL-E are associated with increased morbidity (including prolonged hospital stay), increased healthcare costs, and higher mortality rates compared to infections with non- ESBL-E (Blomberg et al, 2005;Zaoutis et al, 2005;Kim et al, 2002;Ndir et al, 2016). Among neonates, children, and pregnant/ post-partum women, ESBL-E are frequently implicated in urinary tract infections (UTI) (Pitout et al, 2005;Peirano and Pitout, 2010) and bloodstream infections (BSI) (Luvsansharav et al, 2011;Flokas et al, 2017;Dramowski et al, 2015;Zaoutis et al, 2005;Loh and Sivalingam., 2007). Among neonatal ESBL-E infections, Klebsiella pneumoniae and Escherichia coli are the most frequently isolated species (Flokas et al, 2017;Dramowski et al, 2015;Zaidi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En los últimos años se ha evidenciado un incremento notable en la prevalencia de enterobacterales productores de BLEE, tanto a nivel hospitalario como comunitario. 12 Entre los factores de riesgo asociados (2) Cuando se indique tratamiento oral, no existe solución de clindamicina comercializada en algunos países, por lo que cotrimoxazol constituye una posible alternativa.…”
Section: Epidemiologíaunclassified
“…Recently, some laboratories abandoned ESBL testing for therapeutic purposes, in the belief that lowered breakpoints of certain cephalosporins and aztreonam eliminated the risk of therapeutic failures with these drugs (4,5). This has created controversy over whether ESBL testing is really warranted (6)(7)(8)(9)(10)(11)(12)(13)(14). Irrespective of the debate about the value of ESBL testing, laboratories that continue to test must cope with some unresolved issues.…”
mentioning
confidence: 99%